Antiplatelet Management for Stent-Assisted Coiling and Flow Diversion of Ruptured Intracranial Aneurysms: A DELPHI Consensus Statement - Ospel, J.M.; Brouwer, P.; Dorn, F.; Arthur, A.; Jensen, M.E.; Nogueira, R.; Chapot, R.; Albuquerque, F.; Majoie, C.; Jayaraman, M.; Taylor, A.; Liu, J.; et al. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: There is a paucity of data regarding antiplatelet management strategies in the setting of stent-assisted coiling/flow diversion for ruptured intracranial aneurysms. This study aimed to identify current challenges in antiplatelet management during stent-assisted coiling/flow diversion for ruptured intracranial aneurysms and to outline possible antiplatelet management strategies.MATERIALS AND METHODS: The modified DELPHI approach with an on-line questionnaire was sent in several iterations to an international, multidisciplinary panel of 15 neurointerventionalists. The first round consisted of open-ended questions, followed by closed-ended questions in the subsequent rounds. Responses were analyzed in an anonymous fashion and summarized in the final manuscript draft. The statement received endorsement from the World Federation of Interventional and Therapeutic Neuroradiology, the Japanese Society for Neuroendovascular Therapy, and the Chinese Neurosurgical Society.RESULTS: Data were collected from December 9, 2019, to March 13, 2020. Panel members achieved consensus that platelet function testing may not be necessary and that antiplatelet management for stent-assisted coiling and flow diversion of ruptured intracranial aneurysms can follow the same principles. Preprocedural placement of a ventricular drain was thought to be beneficial in cases with a high risk of hydrocephalus. A periprocedural dual, intravenous, antiplatelet regimen with aspirin and a glycoprotein IIb/IIIa inhibitor was preferred as a standard approach. The panel agreed that intravenous medication can be converted to oral aspirin and an oral P2Y12 inhibitor within 24 hours after the procedure.CONCLUSIONS: More and better data on antiplatelet management of patients with ruptured intracranial aneurysms undergoing stent-assisted coiling or flow diversion are urgently needed. Panel members in this DELPHI consensus study preferred a periprocedural dual-antiplatelet regimen with aspirin and a glycoprotein IIb/IIIa inhibitor.GPIIb/IIIaglycoprotein IIb/IIIa receptor